2018
DOI: 10.1038/s41467-018-04804-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic metabolism is essential for CCR7 oligomerization and dendritic cell migration

Abstract: Dendritic cells (DCs) are first responders of the innate immune system that integrate signals from external stimuli to direct context-specific immune responses. Current models suggest that an active switch from mitochondrial metabolism to glycolysis accompanies DC activation to support the anabolic requirements of DC function. We show that early glycolytic activation is a common program for both strong and weak stimuli, but that weakly activated DCs lack long-term HIF-1α-dependent glycolytic reprogramming and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
184
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(189 citation statements)
references
References 42 publications
5
184
0
Order By: Relevance
“…Activation REVIEW SERIES: TRANSLATING IMMUNOMETABOLISM of DCs, either by antigen exposure or stimulation by Toll-like receptor (TLR) ligands, results in a two-phased metabolic shift comprised of an initial glycolytic shift with maintained OXPHOS, followed by elevated glycolysis and the cessation of OXPHOS in long-term activated DCs. Molecularly, TBK-IKKε/AKT signalling pathways and downstream target mammalian target of rapamycin (mTOR) have been strongly implicated in early activation of the glycolytic shift, which can be prevented by adhesion-related kinase (ARK) blockade [62]. Inhibition of glycolysis via HK2 blockade or fatty acid synthase in lipopolysaccharide (LPS)stimulated DCs results in a marked reduction in DC activation and immunogenicity [60].…”
Section: The Role Of Metabolism In DC Activation In Ramentioning
confidence: 99%
See 3 more Smart Citations
“…Activation REVIEW SERIES: TRANSLATING IMMUNOMETABOLISM of DCs, either by antigen exposure or stimulation by Toll-like receptor (TLR) ligands, results in a two-phased metabolic shift comprised of an initial glycolytic shift with maintained OXPHOS, followed by elevated glycolysis and the cessation of OXPHOS in long-term activated DCs. Molecularly, TBK-IKKε/AKT signalling pathways and downstream target mammalian target of rapamycin (mTOR) have been strongly implicated in early activation of the glycolytic shift, which can be prevented by adhesion-related kinase (ARK) blockade [62]. Inhibition of glycolysis via HK2 blockade or fatty acid synthase in lipopolysaccharide (LPS)stimulated DCs results in a marked reduction in DC activation and immunogenicity [60].…”
Section: The Role Of Metabolism In DC Activation In Ramentioning
confidence: 99%
“…During the later stages of DC activation, mTOR-mediated induction of inducible nitric oxide synthase (iNOS) and stabilization of HIF-1α is important for the complete commitment of activated DCs to glycolysis [59,62], with iNOSderived nitric oxide (NO) blocking the electron transport chain (ETC) and sequestering OXPHOS [59] while elevating HIF1α-dependent glycolytic gene expression [62,63,65]. While these metabolic changes remain to be studied in the complex nutrient and/or oxygen-deprived microenvironments, such as those found in the inflamed synovium, similar to macrophages, DC can also sense and respond to extracellular metabolites, such as succinate, butyrate and ATP [33,[66][67][68][69] to potentially trigger a co-ordinated cellular response reflective of the metabolic state of the surrounding microenvironment.…”
Section: The Role Of Metabolism In DC Activation In Ramentioning
confidence: 99%
See 2 more Smart Citations
“…Ricciardi et al recapitulated these results, showing that monocyte-derived immature DCs grown in hypoxia developed a strong migratory phenotype while dampening proinflammatory cytokine secretion [99]. Guak and colleagues linked this phenomenon to metabolism by demonstrating that both strong and weak stimuli will induce glycolysis in DCs, but only strongly proinflammatory signals will stabilize HIF-1α, leading to a prolonged reprogramming of DC metabolism towards glycolysis [100]. Furthermore, Jantsch et al showed that immature DCs stimulated with LPS under hypoxia, compared to normoxia, have a dramatic increase in T cell costimulatory molecule expression that leads to enhanced lymphocyte proliferation [101].…”
Section: Mechanisms Of Hif-1α Stabilization Activation and Degradatmentioning
confidence: 99%